2014
DOI: 10.1016/j.ijgo.2014.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health and HIV awareness among newly married Egyptian couples without formal education

Abstract: Routine premarital counseling and testing by reproductive health, gynecology, and andrology specialists need to be enforced. Mass media is an essential source of knowledge about HIV and reproductive health. Premarital, reproductive health, and HIV education programs need to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
(8 reference statements)
0
11
0
1
Order By: Relevance
“…Fifty one included studies assessed the awareness of 1,235,811 Africans in regard to HIV in total of 35 countries, eleven studies were conducted in Nigeria [14,16,83,17,18,23,38,48,60,63,81] , nine in South Africa [24,27,29,34,37,42,46,82,84] , five in each of Ghana [19,31,65,66,68] and Ethiopia [21,73,77,78,80] , four in Uganda [13,55,72,75] , three in Mozambique [22,26,30] , two in each of Namibia [45,76] and Cameroon [59,67] , one in each of Congo [25] , Sudan [33] , Senegal [39] , Morocco [47] , Gambia [50] , Tanzania [53] , Madagascar [71] and Egypt [74] while a study provided awareness prevalence in 33 countries [8] . The conduction of the studies ranged from 2010 to 2017.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifty one included studies assessed the awareness of 1,235,811 Africans in regard to HIV in total of 35 countries, eleven studies were conducted in Nigeria [14,16,83,17,18,23,38,48,60,63,81] , nine in South Africa [24,27,29,34,37,42,46,82,84] , five in each of Ghana [19,31,65,66,68] and Ethiopia [21,73,77,78,80] , four in Uganda [13,55,72,75] , three in Mozambique [22,26,30] , two in each of Namibia [45,76] and Cameroon [59,67] , one in each of Congo [25] , Sudan [33] , Senegal [39] , Morocco [47] , Gambia [50] , Tanzania [53] , Madagascar [71] and Egypt [74] while a study provided awareness prevalence in 33 countries [8] . The conduction of the studies ranged from 2010 to 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Media (as general) was the main source of information of participants reported in several studies [17,47,74] . However, other studies among students reported that school is the main source of information not media [22,75] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Awareness of HIV related to demographic characteristics. Media (as general) was the main source of information of participants reported in several studies [17,47,74]. However, other studies among students reported that school is the main source of information not media [22,75].…”
Section: Year Of Publicationmentioning
confidence: 97%